Improving the energy resolution of bent crystal X‐ray spectrometers with position‐sensitive detectors. (11th June 2014) - Honkanen, Ari‐Pekka; Verbeni, Roberto; Simonelli, Laura; Moretti Sala, Marco; Al‐Zein, Ali; Krisch, Michael; Monaco, Giulio; Huotari, Simo
<x xml:space="preserve">Abstract</x> Wavelength‐dispersive high‐resolution X‐ray spectrometers often employ elastically bent crystals for the wavelength analysis. In a preceding paper [Honkanen et al. (2014). J. Synchrotron Rad.21, 104–110] a theory for quantifying the internal stress of a macroscopically large spherically curved analyser crystal was presented. Here the theory is applied to compensate for the corresponding decrease of the energy resolution. The technique is demonstrated with a Johann‐type spectrometer using a spherically bent Si(660) analyser in near‐backscattering geometry, where an improvement in the energy resolution from 1.0 eV down to 0.5 eV at 9.7 keV incident photon energy was observed.